2017
DOI: 10.3389/fpsyt.2017.00109
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Coupling between the Dorsomedial Prefrontal Cortex and the Amygdala in Schizophrenia Smokers Viewing Anti-smoking Images

Abstract: BackgroundCigarette smoking is highly prevalent in schizophrenia and is one of the main factors contributing to the significantly decreased life expectancy in this population. Schizophrenia smokers, compared to their counterparts with no comorbid psychiatric disorder, are largely unaware and indifferent to the long-term negative consequences of cigarette smoking. The objective of this study was to determine, for the first time, if these meta-cognitive deficits are associated with neuro-functional alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Jung et al (2013) reported that right amygdala activation was positively correlated with individuals’ probability of choosing high-value items for themselves, while the activity of the left dorsomedial prefrontal cortex (DMPFC) was positively correlated with the probability of choosing high-value items for strangers. In addition, further analysis found a stronger functional connectivity between the rTPJ and the left DMPFC in decision making for others than that for oneself (Jung et al, 2013), while amygdala activation could be regulated by the DMPFC through the functional connectivity between these two brain areas (Banks et al, 2007; Phillips et al, 2008; Leiberg et al, 2011; Potvin et al, 2017). Brain imaging studies of risky decision making have found that the amygdala is not only sensitive to potential loss in decision making but also closely related to loss aversion (Bechara et al, 1999; De Martino et al, 2010; Sokolhessner et al, 2013; Phelps et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Jung et al (2013) reported that right amygdala activation was positively correlated with individuals’ probability of choosing high-value items for themselves, while the activity of the left dorsomedial prefrontal cortex (DMPFC) was positively correlated with the probability of choosing high-value items for strangers. In addition, further analysis found a stronger functional connectivity between the rTPJ and the left DMPFC in decision making for others than that for oneself (Jung et al, 2013), while amygdala activation could be regulated by the DMPFC through the functional connectivity between these two brain areas (Banks et al, 2007; Phillips et al, 2008; Leiberg et al, 2011; Potvin et al, 2017). Brain imaging studies of risky decision making have found that the amygdala is not only sensitive to potential loss in decision making but also closely related to loss aversion (Bechara et al, 1999; De Martino et al, 2010; Sokolhessner et al, 2013; Phelps et al, 2014).…”
Section: Discussionmentioning
confidence: 97%